Dear Evan Hansen [videorecording (DVD)] - Chbosky, Stephen; Platt, Ben; Moore, Julianne; Dever, Kaitlyn; Pasek, Benj; Paul, Justin, 1985- (SDS, 2021)
A high school senior struggling with social anxiety disorder goes on a journey of self-discovery in the wake of a fellow student's suicide.